Revisiting a summer vacation: digital restoration and typesetter forensics - Bagley, Steven R.; Brailsford, David F.; Kernighan, Brian W. (2013)
In 1979 the Computing Science Research Center (‘Center 127’) at Bell Laboratories bought a Linotron 202 typesetter from the Mergenthaler company. This was a ‘third generation’ digital machine that used a CRT to image characters onto photographic paper.